(untitled) (Revista horizonte, 2015)
Currently, legislation and world organizations advocate for inclusion, based on this need the various organizations are concerned about developing strategies and action plans that allow the inclusion of the broad spectrum of special populations. The objective was to know the criteria of a management model of excellence that guide the management of Physical Activity and Sports for the inclusion of children with Asperger Syndrome in private sports institutions in the Province of Concepción. A questionnaire of 22 closed questions applied to sports managers of private sports institutions was used. The results indicate that accesses, signage and exclusive hygienic services are adequately developed, in addition to presenting high adherence to non-discrimination, there is interest in knowing the population with disabilities that each institution has, on the contrary, there is a low importance to the training of professionals to meet special educational needs, leadership, measurement of satisfaction of users with disabilities, development of corporate responsibility and linkage with the environment. It is concluded that there is no formal and systematic use of a management model; on the contrary, there are several criteria developed in a partial way.